Lithium ion battery diaphragm, preparation method thereof and electrochemical device

By using the optimized polymer microsphere particle size distribution and binder characteristic viscosity in lithium-ion battery separators, a coating with high wetting and high liquid retention is formed, which solves the problem of insufficient wetting of the existing separators on the electrolyte and improves the circulation and safety performance of the battery.

CN119812672APending Publication Date: 2025-04-11HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411993611.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have insufficient ion transfer capabilities between electrodes, resulting in insufficient wetting of the electrolyte, affecting the cycling performance and interface compatibility of the battery cell.

Method used

A lithium-ion battery separator including a base film and a coating is used, which consists of polymer microspheres and binder, the particle size distribution of the polymer microspheres and the intrinsic viscosity of the binder are optimized to form a separator with high wetting and high liquid retention.

Benefits of technology

It improves the circulation and safety performance of lithium-ion batteries, and enhances the adhesive performance with the electrode sheet to ensure sufficient impregnation and liquid retention of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224129830000131
    Figure BDA0005224129830000131
  • Figure BDA0005224129830000141
    Figure BDA0005224129830000141
  • Figure BDA0005224129830000151
    Figure BDA0005224129830000151
Patent Text Reader

Abstract

The invention relates to the technical field of battery diaphragms, in particular to a lithium ion battery diaphragm, a preparation method thereof and an electrochemical device. The lithium ion battery diaphragm comprises a base membrane and a coating formed on at least one surface of the base membrane, and the coating comprises polymer microspheres and a binder; wherein the particle size D90 of the polymer microspheres is a [mu] m, the particle size D50 is b [mu] m, the particle size D10 is c [mu] m, the intrinsic viscosity of the binder is d dL / g, and a / d is greater than or equal to 3.2 and less than or equal to 175, b / d is greater than or equal to 1.2 and less than or equal to 55, and c / d is greater than or equal to 0.4 and less than or equal to 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery separators, and in particular to a lithium-ion battery separator and a preparation method thereof, and an electrochemical device. Background Art

[0002] Secondary batteries (lithium-ion) are one of the most advanced energy storage devices currently available because they have high energy density, are environmentally safe, and have a long lifespan. However, conventional lithium-ion batteries (LIBs) using liquid electrolytes have some disadvantages, namely, safety hazards (e.g., safety issues caused by leakage of liquid electrolytes), flexibility issues, and poor interfacial compatibility between electrolytes and electrodes. Therefore, in the current LIB industry, microporous polypropylene membranes are used as separators, where the microporous structure can effectively store electrolytes, and at the same time, this diaphragm avoids physical contact between the cathode and the anode. However, this diaphragm must also have the ability to transfer ions between the electrodes. In addition, to be used as a battery, the polymer electrolyte must be sandwiched between the battery electrodes, and conventional diaphragms are coated with ceramic coatings, resulting in insufficient wettability to the electrolyte, so that the battery cell cannot achieve high-rate cycling.

[0003] In order to improve the safety, capacity and cycle life of batteries, the adhesion of the diaphragm to the electrode and the electrolyte absorption and retention have become the focus of research. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium ion battery separator.

[0005] The invention also provides a method for preparing the lithium ion battery separator.

[0006] The present invention also provides an electrochemical device comprising the lithium ion battery separator.

[0007] The lithium ion battery separator of the present invention has high wettability and high liquid retention, can improve the bonding performance with the pole piece, and can improve the cycle performance and safety performance of the lithium ion battery.

[0008] According to an embodiment of the first aspect of the present invention, there is provided a lithium ion battery separator, comprising a base film and a coating formed on at least one surface of the base film, wherein the coating comprises polymer microspheres and a binder;

[0009] Wherein, the particle size D90 of the polymer microsphere is a μm, the particle size D50 of the polymer microsphere is b μm, the particle size D10 of the polymer microsphere is c μm, and the intrinsic viscosity of the binder is d dL / g, satisfying:

[0010] 3.2≤a / d≤175, 1.2≤b / d≤55, and 0.4≤c / d≤10.

[0011] The present invention defines the ratio between the particle size of the polymer microspheres and the intrinsic viscosity of the binder. When the particle size of the polymer microspheres is too large and the intrinsic viscosity of the binder is too small, the binder will undergo a phase inversion process during coating and powder will fall off, affecting the coating processability. On the contrary, when the particle size of the polymer microspheres is too small and the intrinsic viscosity of the binder is too large, the thickness of the coated diaphragm will be too small. After the hot pressing and forming process of the battery core, the pores of the formed coating are too small, which is not conducive to the storage of electrolyte and affects the cycle performance and interface of the battery core. When the above ratio limit is met, these problems can be effectively overcome.

[0012] According to some embodiments of the present invention, the material of the polymer microspheres is selected from at least one of polyethylene, acrylate copolymers (such as polymethyl methacrylate), polystyrene, polyacrylamide, polylactic acid copolymers, polycaprolactone, or modified polymers thereof.

[0013] According to some embodiments of the present invention, the particle size D10 of the polymer microspheres is 1 to 2 μm, for example, 1.0 to 1.5 μm.

[0014] According to some embodiments of the present invention, the particle size D50 of the polymer microspheres is 3 to 11 μm, for example, 4 to 10 μm, 5.0 to 9.0 μm, 6.0 to 9.0 μm, or 8.0 to 9.0 μm.

[0015] According to some embodiments of the present invention, the particle size D90 of the polymer microspheres is 8 to 35 μm, for example, 8 to 30 μm, 8 to 25 μm, 9.0 to 20 μm, 12 to 20 μm, or 15 to 20 μm.

[0016] According to some embodiments of the present invention, the polymer microspheres are compressible. Exemplarily, the compressibility test method of the polymer microspheres includes: hot pressing for 1 hour at 85° C. and a pressure of 1 MPa, testing 5 points, and comparing the thickness change of the diaphragm before and after hot pressing to evaluate the compressibility.

[0017] According to some embodiments of the present invention, the intrinsic viscosity of the binder is 0.2-2.5 dL / g, for example, 0.2-1.5 dL / g, 0.2-1.2 dL / g, 0.2-1.0 dL / g, 0.2-0.8 dL / g, 0.2-0.6 dL / g, 0.2-0.4 dL / g.

[0018] The intrinsic viscosity of the binder is positively correlated with its molecular weight. The larger the intrinsic viscosity of the binder, the larger its molecular weight. When preparing a casting solution with the same composition at the same dissolution temperature, the greater the degree of mutual entanglement of the polymer chains in the solution. That is, the greater the viscosity of the casting solution with the same solid content, the shorter the time required for the casting solution to solidify into a film by phase separation. In short, since the larger the molecular weight of the binder, the greater the viscosity of the casting solution, the curing speed of the binder-rich phase is greater than the relaxation time of the binder molecules, and strong binder molecules remain at the phase interface. Under the action of stress, cracks are generated at the phase interface and grow. As the concentrated binder phase solidifies, an interconnected sponge-like structure is formed. When the intrinsic viscosity of the binder is too low, the molecular weight of the corresponding binder is low, and the adhesion of the coating applied to the base film after the coagulation bath is also low, which easily causes the coating to fall off.

[0019] According to some embodiments of the present invention, the molecular weight of the binder is between 100,000 and 1.5 million.

[0020] According to some embodiments of the present invention, the swelling rate of the binder in the electrolyte is 20% to 60%, for example, 20% to 50%, 20% to 45%, 20% to 40%, 20% to 35%, 25% to 40%, 30% to 40%.

[0021] Too high a swelling rate of the binder in the electrolyte will affect the transmission of lithium ions and thus the cycle performance of the battery cell.

[0022] According to some embodiments of the present invention, the binder is selected from at least one of vinylidene fluoride homopolymer (polyvinylidene fluoride), copolymer of vinylidene fluoride and other copolymerizable monomers (for example, one or more of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, trichloroethylene, chlorotrifluoroethylene, vinyl fluoride, monomethyl maleate), polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, and polyphenylene ether.

[0023] According to some embodiments of the present invention, the weight proportion of the polymer microspheres in the coating is 10% to 80%, for example, 20% to 70%, 30% to 70%, 40% to 70%, 50% to 70%, 60% to 70%.

[0024] According to some embodiments of the present invention, the weight proportion of the binder in the coating is 20% to 90%, for example, 20% to 80%, 20% to 70%, 20% to 40%, 30% to 60%, 30% to 50%.

[0025] According to some embodiments of the present invention, a weight ratio of the polymer microspheres to the binder is 1:3 to 3:1, for example, 1:2.5 to 2.5:1, 1:2 to 2:1.

[0026] When the weight ratio of the two is less than 1:3, the proportion of polymer microspheres is too small, the amount of polymer microspheres during coating is too small, and the compressibility is not obvious; when the weight ratio is greater than 3:1, there are too many polymer microspheres, and after being subjected to pressure, the distance between the microspheres decreases, which affects the transmission of lithium ions. Moreover, when the weight ratio is greater than 3:1, the network entanglement structure of the adhesive is not sufficient to entangle the polymer microspheres, and there is a risk of powder falling during coating.

[0027] According to some embodiments of the present invention, the coating optionally further comprises a pore-forming additive.

[0028] According to some embodiments of the present invention, the pore-forming additive is selected from at least one of polyethylene glycol, polyvinyl pyrrolidone, LiCl, dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate and diisobutyl phthalate.

[0029] According to some embodiments of the present invention, the weight percentage of the pore-forming additive in the coating is 0.01% to 5%.

[0030] According to some embodiments of the present invention, the material of the base film is selected from at least one of PE, PP, and a composite of PE and PP.

[0031] The present invention does not impose any particular limitation on the melting point of the base film, and for example, the melting point may be 130 to 160°C.

[0032] According to some embodiments of the present invention, the base film has a thickness of 3 μm to 20 μm, for example, 3 μm to 15 μm, 3 μm to 10 μm, 3 μm to 8 μm, or 4 μm to 5 μm.

[0033] According to some embodiments of the present invention, the base film has a porous structure, and the porosity of the base film is 20% to 50%, for example, 25% to 45%, 30% to 40%.

[0034] According to some embodiments of the present invention, the air permeability of the base film is 30 to 400 sec / 100 cc, for example, 50 to 400 sec / 100 cc, 100 to 300 sec / 100 cc, 120 to 250 sec / 100 cc, 150 to 250 sec / 100 cc, or 200 to 250 sec / 100 cc.

[0035] According to some embodiments of the present invention, the structural morphology of the formed coating includes one or more of a cellular structure (eg, a hilly ridge structure), a granular structure, a bicontinuous structure, a latex structure, and a macroporous structure.

[0036] According to some embodiments of the present invention, the coating has a thickness of 1 to 10 μm, such as 2 to 8 μm, 3 to 6 μm, or 3.5 to 5.0 μm.

[0037] According to some embodiments of the present invention, the compression rate of the coating is 10% to 70%, for example, 20% to 70%, 30% to 70%, 35% to 70%, 42% to 70%, 48% to 70%, 53% to 70%, 53% to 60%.

[0038] According to some embodiments of the present invention, the porosity of the coating is 25% to 80%, 30% to 80%, 35% to 80%, 40% to 80%, or 65% to 80%.

[0039] According to an embodiment of the second aspect of the present invention, there is provided a method for preparing the lithium ion battery separator, comprising the following steps:

[0040] The polymer microspheres, the binder and the solvent are mixed to obtain a casting solution; the casting solution is coated on a base film, and then immersed in a coagulation bath to solidify to obtain a primary film, and then the solvent in the primary film is removed to obtain the film.

[0041] According to some embodiments of the present invention, the polymer microspheres are first dispersed in a solvent (for example, at 1000-2000 rpm for 20-40 min), and then the binder is added and mixed (for example, at 500-1000 rpm for 30-90 min) to obtain a casting liquid; further, the casting liquid is coated on at least one surface of the base film, and then immersed in a coagulation bath to cause non-solvent induced phase separation to form a two-phase structure with the polymer as the continuous phase and the solvent as the dispersed phase, and the film is solidified to obtain a primary film, and then the solvent in the primary film is removed through a multi-section water tank.

[0042] According to some embodiments of the present invention, the step further comprises adding the binder and mixing, then adding 0.04 to 0.12 wt % polyvinyl pyrrolidone, and optionally stirring for 10 to 30 minutes.

[0043] According to some embodiments of the present invention, the solvent is selected from at least one of dimethylacetamide (DMAC), dichloroethane, dimethylformamide (DMF), trichloroethane, chloroform, ethyl acetate, sulfolane, dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), chloroform, dichloromethane and acetone. Under normal temperature conditions, a suitable solvent is selected to dissolve the binder to form a homogeneous solution, which is then transferred to a non-solvent phase to form a film. The solvent of the present invention is easily dissolved in water and undergoes a displacement reaction with water to obtain a porous membrane structure.

[0044] According to some embodiments of the present invention, the concentration of the casting solution is 2% to 12%, for example, 2% to 10%, 2% to 8%, 2% to 6%, 2% to 4%, 2% to 3%. In the rapid phase separation system of solvent / non-solvent interaction, the formation of the cortex is mainly controlled by thermodynamic properties. At low concentrations (<12wt%), the phase separation of the cortex is mainly instantaneous liquid-liquid phase separation; when the concentration is high (>12wt%), the phase separation of the cortex is mainly liquid-solid phase separation, generating a dense granular surface.

[0045] Under the conditions of suitable intrinsic viscosity of the binder and casting solution concentration, the formed coating is a macroporous interconnected interlocking structure, the secondary particles of the polymer microspheres form hills, and the polymer microspheres are connected to the hills to form a hilly structure covered by multiple interconnected circular ridges. Under the conditions of suitable intrinsic viscosity of the binder and casting solution concentration, if the particle size of the polymer microspheres is too small, it will affect the formation of the above structure; if the particle size of the polymer microspheres is too large, it will affect the coating processability.

[0046] According to some embodiments of the present invention, the coagulation bath comprises water and a non-aqueous solvent, wherein the non-aqueous solvent is selected from one or more of dimethylacetamide (DMAC), dichloroethane, dimethylformamide (DMF), trichloroethane, chloroform, ethyl acetate, sulfolane, dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), chloroform, dichloromethane and acetone.

[0047] According to some embodiments of the present invention, in the coagulation bath, the volume ratio of water to the non-aqueous solvent is 2 to 6:1.

[0048] The porous structure of the membrane is formed as follows: after the casting liquid is coated, it is passed through a roller and immersed in a coagulation bath, and phase separation occurs through the double diffusion between the solvent and the non-solvent, and then solidifies to form a porous membrane. When the ratio is greater than 6, the pore size formed is too large and discontinuous, which is not conducive to electrolyte retention; when the ratio is less than 2, the pore size formed is too small, and too much waste liquid in the coagulation tank is generated during the production process, increasing the cost of waste liquid treatment.

[0049] According to some embodiments of the present invention, the temperature of the coagulation bath is 20-50°C.

[0050] In a film-making system with strong solvent / non-solvent interaction and fast diffusion, the film-forming process and the structural properties of the film are mainly controlled by the kinetic diffusion process; at this time, the thermodynamic properties of the casting solution have little effect on the film formation. Crystalline binders affect the film-forming kinetics at low temperatures and slow down the film-forming speed. When the temperature is greater than 50°C, the production cost increases. Considering the structure of the film and the energy consumption cost, the temperature range of the coagulation bath is preferably 25°C to 35°C.

[0051] According to some embodiments of the present invention, the coating method is selected from one or more of micro-gravure coating, extrusion coating, dip coating, spray coating, dot matrix coating and wire rod coating.

[0052] According to an embodiment of the third aspect of the present invention, there is provided an electrochemical device comprising a positive electrode, a negative electrode, an electrolyte and the above-mentioned lithium-ion battery separator.

[0053] The present invention does not specifically limit the positive electrode. Exemplarily, the positive electrode may include a positive electrode collector and a positive electrode material layer. The positive electrode collector is used to carry the positive electrode material layer and conduct current, and the shape may be a foil or a mesh. The material of the positive electrode collector may be selected from aluminum, titanium or stainless steel. The positive electrode material layer is disposed on at least one surface of the positive electrode collector. The positive electrode material layer includes a positive electrode active material, and may further include a conductive agent and a binder. The conductive agent and the binder may be uniformly mixed with the positive electrode active material. The material of the positive electrode is lithium cobalt oxide, nickel cobalt manganese or nickel cobalt aluminum ternary positive electrode material, and the molecular formulas are LiCoO2 (lithium cobalt oxide), LiNi x Mn y Co z O2 (nickel manganese cobalt ternary positive electrode) and LiNi x Mn y Al z O2 (nickel-manganese-aluminum ternary positive electrode), 0.50≤x<1.00, 0<y≤0.30, 0<z≤0.20, etc.

[0054] The present invention does not specifically limit the negative electrode. Exemplarily, the negative electrode may include a negative electrode current collector and a negative electrode material layer. The negative electrode current collector is used to carry the negative electrode material layer and conduct current, and the shape may be a foil or a mesh. The material of the negative electrode current collector may be selected from copper, nickel or stainless steel. The negative electrode material layer is disposed on at least one surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material, and may further optionally include a conductive agent and a binder. The conductive agent and the binder may be uniformly mixed with the negative electrode active material. The negative electrode active material may be at least one of graphite, hard carbon, silicon carbide, silicon oxide, etc.

[0055] The present invention does not particularly limit the electrolyte. Exemplarily, the electrolyte includes a solvent and a lithium salt solute dissolved in the solvent. The solvent can be selected from one or more of cyclic carbonates, chain carbonates, cyclic ethers, chain ethers, nitriles and amides, such as ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, diethyl ether, acetonitrile, propionitrile, anisole, butyrate, glutaronitrile, hexamethylenenitrile, γ-butyrolactone, γ-valerolactone, tetrahydrofuran, 1,2-dimethoxyethane, acetonitrile and dimethylformamide. One or more. The lithium salt solute can be selected from one or more of lithium chloride (LiCl), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4) and lithium bis(oxalatoborate) (LiBOB).

[0056] According to some embodiments of the present invention, there are at least the following beneficial effects:

[0057] The coating of the present invention is a viscous porous layer, in which the polymer microspheres and the binder provide adhesion to the pole piece, and the pores mainly provide ion permeation channels; in addition, the polymer microspheres also provide a certain compressibility, which can ensure a certain gap after the battery cell is formed and hot-pressed.

[0058] The organic coating formed by the present invention is a macroporous interconnected interlocking structure, the secondary particles of the polymer microspheres form a hilly shape, the microspheres are connected to the hills, forming a plurality of interconnected circular ridges covering the hills, and this structure is beneficial to improving the liquid retention of the diaphragm and also to improving the adhesion with the electrode.

[0059] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0061] Figure 1 is the electrolyte diffusion diagram in Example 2;

[0062] Figure 2 This is the electrolyte diffusion diagram in Comparative Example 1. DETAILED DESCRIPTION

[0063] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0064] In the description of the present invention, it should be noted that, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.

[0065] In the description of the present invention, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0066] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0067] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0068] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0069] Exemplarily, the testing methods of various performances and physicochemical parameters involved in the present invention include:

[0070] (1) Intrinsic viscosity of the binder: measured using an Ubbelohde viscometer at 25°C, with the binder diluted to a solid content of 0.005 g / mL;

[0071] (2) Swelling rate of the binder: Dry the binder and cut it into a 12 mm diameter and 1 mm thick binder sheet. Put the prepared binder sheet into a glove box for swelling rate test. Immerse the sheet in electrolyte (1 mol / L LiPF6, EC:PC:DEC:PP=2:2:3:3), let it stand in the glove box for 72 hours, then take out the sheet and weigh the mass as W1; dry it and weigh the mass of the dried sheet as W2. The swelling rate is calculated as: W2 / W1×100%;

[0072] (3) Particle size of microspheres: measured by laser diffraction method; D10 refers to the equivalent diameter of the largest particle when the cumulative distribution is 10% in the particle size distribution curve, D50 refers to the equivalent diameter of the largest particle when the cumulative distribution is 50% in the particle size distribution curve, and D90 refers to the equivalent diameter of the largest particle when the cumulative distribution is 90% in the particle size distribution curve;

[0073] (4) Porosity of base film: can be tested according to the method specified in GB / T36363-2018;

[0074] (5) Air permeability of base film: It can be tested according to the method specified in GB / T 36363-2018, and the air permeability test instrument is Asahi Seiko G-500;

[0075] (6) Coating compression rate: The initial thickness of the freshly coated separator h0 and the corresponding separator substrate thickness h, positive electrode thickness m, and negative electrode thickness n are tested with a micrometer. A layer of positive electrode, a layer of separator, and a layer of negative electrode are stacked, and then hot pressed. The overall thickness of the positive electrode + separator + negative electrode unit after hot pressing is tested. Separator coating compression rate = 1-(smnh) / (h0-h).

[0076] Example 1

[0077] This embodiment provides a method for preparing a lithium ion battery separator, comprising the following steps:

[0078] S1. Preparation of slurry: Take 98 parts by weight of N-methylpyrrolidone, add 1.4 parts by weight of polymethyl methacrylate (PMMA) microspheres (particle size D90 is about 19.20 μm, particle size D50 is about 8.95 μm, particle size D10 is about 1.45 μm, purchased from Shanghai Tefubang New Material Technology Co., Ltd.), and stir at 1500 rpm for 30 minutes; then add 0.6 parts by weight of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) (intrinsic viscosity is 0.2 dL / g, swelling rate is 35%, purchased from Arkema, LBG), and stir at 1000 rpm for 60 minutes; add 0.08‰ weight part of polyvinylpyrrolidone (PVP) to the slurry, stir for 20 minutes, and obtain a casting solution (concentration is 2%).

[0079] S2. The casting liquid prepared in step S1 is coated on a polyethylene (PE) base film (porosity of 38%, air permeability of 145 sec / 100 cc) through a micro-gravure roller, and the coating thickness is 4.5 μm. It is then immersed in a coagulation bath (deionized water and N-methylpyrrolidone are mixed in a volume ratio of 80:20) to cause non-solvent induced phase separation. After the phase separation reaction, the precipitated diaphragm is washed with water in 4 water tanks, and then dried in an oven at 45°C and rolled up to obtain a diaphragm.

[0080] Example 2

[0081] The present embodiment provides a method for preparing a lithium-ion battery separator, which is carried out in reference to Example 1, with the only difference being that the amount of PMMA microspheres added is 1.2 parts by weight, the amount of PVDF-HFP added is 0.8 parts by weight, and the PE film is replaced by a polypropylene (PP) film (porosity is 30%, air permeability is 250sec / 100cc).

[0082] Example 3

[0083] This embodiment provides a method for preparing a lithium-ion battery separator, which is carried out in Reference Example 1, except that the amount of PMMA microspheres added is 0.8 parts by weight and the amount of PVDF-HFP added is 1.2 parts by weight.

[0084] Example 4

[0085] This embodiment provides a method for preparing a lithium-ion battery separator, which is carried out in reference to Example 2, except that the amount of PMMA microspheres added is 0.6 parts by weight and the amount of PVDF-HFP added is 1.4 parts by weight.

[0086] Example 5

[0087] This embodiment provides a method for preparing a lithium-ion battery separator, which is carried out in reference to Example 1, except that the amount of PMMA microspheres added is 0.2 parts by weight and the amount of PVDF-HFP added is 1.8 parts by weight.

[0088] Example 6

[0089] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in Reference Example 2, except that PMMA microspheres are replaced with polystyrene (PS) microspheres (particle size D90 is about 13.20 μm, particle size D50 is about 5.95 μm, and particle size D10 is about 1.05 μm), which are purchased from Xianfeng Nano, brand XFJ100.

[0090] Example 7

[0091] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in Reference Example 2, except that PMMA microspheres are replaced with polyacrylamide (PAM) microspheres (particle size D90 is about 9.87 μm, particle size D50 is about 5.46 μm, and particle size D10 is about 1.20 μm), which are purchased from DeLan Chemical with the brand name NPAM.

[0092] Example 8

[0093] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 1, except that PMMA microspheres are replaced with PS microspheres (particle size D90 is about 13.20 μm, particle size D50 is about 5.95 μm, and particle size D10 is about 1.05 μm).

[0094] Example 9

[0095] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 2, with the only difference being that PVDF-HFP is replaced by polyimide (with a characteristic viscosity of 0.6 dL / g and a swelling ratio of 21%), purchased from Shenzhen Zhibang Technology Co., Ltd., with the brand name BPR-100.

[0096] Example 10

[0097] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 3, with the only difference being that PVDF-HFP is replaced with polyamide (with a characteristic viscosity of 1.2 dL / g and a swelling ratio of 43%), purchased from Jiangsu Tengyue New Material Technology, with a brand name of PA66.

[0098] Embodiment 11

[0099] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 6, except that PVDF-HFP is replaced by polyimide (with a characteristic viscosity of 0.6 dL / g and a swelling ratio of 21%).

[0100] Example 12

[0101] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 7, except that PVDF-HFP is replaced by polyimide (with a characteristic viscosity of 0.6 dL / g and a swelling ratio of 21%).

[0102] Embodiment 13

[0103] The present embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 5, with the only difference being that PMMA microspheres are replaced with PS microspheres (particle size D90 is approximately 13.20 μm, particle size D50 is approximately 5.95 μm, and particle size D10 is approximately 1.05 μm), and at the same time, PVDF-HFP is replaced with polyamide (characteristic viscosity is 1.2 dL / g, and swelling rate is 43%).

[0104] Embodiment 14

[0105] This embodiment provides a preparation process of a lithium ion battery separator, which is carried out in reference to Example 2, except that:

[0106] Take 90 parts by weight of N-methylpyrrolidone, add 6 parts by weight of PMMA microspheres, and add 4 parts by weight of PVDF-HFP.

[0107] Embodiment 15

[0108] This embodiment provides a preparation process of a lithium-ion battery separator, which is carried out in reference to Example 1, except that:

[0109] Take 80 parts by weight of N-methylpyrrolidone, add 12 parts by weight of PMMA microspheres, and add 8 parts by weight of PVDF-HFP.

[0110] Example 16

[0111] This embodiment provides a preparation process of a lithium ion battery separator, which is carried out in reference to Example 2, except that:

[0112] Take 99.5 parts by weight of N-methylpyrrolidone, add 0.25 parts by weight of PMMA microspheres, and add 0.25 parts by weight of PVDF-HFP.

[0113] Embodiment 17

[0114] This embodiment provides a preparation process of a lithium ion battery separator, which is carried out in reference to Example 11, except that:

[0115] The coagulation bath consisted of a mixture of deionized water and dimethylformamide in a volume ratio of 95:5.

[0116] Embodiment 18

[0117] This embodiment provides a preparation process of a lithium ion battery separator, which is carried out in reference to Example 12, except that:

[0118] The coagulation bath consisted of a mixture of deionized water and N-methylpyrrolidone in a volume ratio of 50:50.

[0119] The coating of the lithium-ion battery separator prepared in Examples 1-18 includes polymer microspheres and a binder. After testing, the particle size D90 of the polymer microspheres ranges from 8 to 35 μm, the particle size D50 ranges from 3 to 11 μm, the particle size D10 ranges from 1 to 2 μm, and the characteristic viscosity of the binder ranges from 0.2 to 2.5 dL / g. The present invention finds that when the ratio of the particle size D90 of the polymer microspheres to the characteristic viscosity is 3.2 to 175, the ratio of the particle size D50 of the polymer microspheres to the characteristic viscosity is 1.2 to 55, and the ratio of the particle size D10 of the polymer microspheres to the characteristic viscosity is 0.4 to 10, the lithium-ion battery separator has excellent performance effects. This is because:

[0120] The particle size D10 of the polymer microspheres is controlled in the range of 1-2μm, and the particle size D90 is controlled in the range of 8-35μm, which can ensure that there is enough gap between the diaphragm and the pole piece, which is conducive to the continuous distribution of the electrolyte, so that the electrolyte can fully infiltrate the pole piece, and at the same time, avoid the influence of excessive particle size on the bonding performance of the coating. To further optimize the particle size distribution, it is necessary to control the particle size D50 in the range of 3-11μm, so that there are appropriate pores between the microspheres, thereby providing a buffer space for the expansion of the diaphragm after infiltration of the electrolyte. In accordance with this, when the characteristic viscosity of the binder is in the range of 0.2-2.5dL / g, it can ensure good adhesion to the microspheres, but the characteristic viscosity should not be too large, otherwise it will be detrimental to subsequent processing. The appropriate characteristic viscosity should ensure that the ratio of the particle size D90, D50, D10 of the polymer microspheres to the characteristic viscosity is within a certain range, which can prevent the viscosity of the binder from being too large and causing the pores to become less.

[0121] Examples 1-18 also each provide a lithium ion battery separator prepared by the above method, including a base film and a coating formed on the surface of one side of the base film. Among them, the thickness of the base film measured in Examples 1-4 and 14 is 4.0-5.0 μm; the coating has a cellular structure, a porosity of 65%-78%, a thickness of 3.7-4.5 μm, the coating is compressible, and the compression rate of the coating is 53%-58%. In Examples 5-12, the thickness of the base film is measured to be 4.0-5.0 μm; the coating has a cellular structure, a porosity of 42%-65%, a thickness of 3.6-5.0 μm, the coating is compressible, and the compression rate of the coating is 48%-66%. In Examples 13, 15-16, the thickness of the base film is measured to be 4.0-5.0 μm; the porosity of the coating is 41-51%, the thickness is 3.6-5.0 μm, the coating is compressible, and the compression rate of the coating is 30-46%. In Examples 17-18, the thickness of the base film was measured to be 4.0-5.0 μm; the coating had a porosity of 35-40%, a thickness of 3.6-5.0 μm, the coating was compressible, and the compression rate of the coating was 38-41%.

[0122] Comparative Example 1

[0123] This comparative example provides a preparation process of a lithium ion battery separator, which is carried out in reference to Example 2, except that:

[0124] The PMMA microspheres were replaced with alumina (particle size D90 was about 1.2 μm, particle size D50 was about 0.5 μm, and particle size D10 was about 0.3 μm).

[0125] Comparative Example 2

[0126] This comparative example provides a preparation process of a lithium-ion battery separator, which is carried out in Reference Example 2, except that the PMMA microspheres have a particle size D90 of about 1.61 μm, a particle size D50 of about 0.95 μm, and a particle size D10 of about 0.76 μm, and are purchased from Xi'an Qiyue Biology, brand Q-0166053.

[0127] Comparative Example 3

[0128] This comparative example provides a preparation process of a lithium-ion battery separator, which is carried out in Reference Example 1, except that the PMMA microspheres have a particle size D90 of about 38.45 μm, a particle size D50 of about 26.24 μm, and a particle size D10 of about 2.38 μm, and are purchased from Dongguan Hongyu Plastics, brand BR116.

[0129] Comparative Example 4

[0130] This comparative example provides a preparation process for a lithium-ion battery separator, which is carried out in reference to Example 2, with the only difference being that 1.2 parts by weight of PMMA microspheres are replaced with 1 part by weight of alumina (particle size D90 is approximately 1.2 μm, particle size D50 is approximately 0.5 μm, and particle size D10 is approximately 0.3 μm) and 0.2 parts by weight of PMMA microspheres (particle size D90 is approximately 1.61 μm, particle size D50 is approximately 0.95 μm, and particle size D10 is approximately 0.76 μm).

[0131] Application Examples

[0132] This application example provides a lithium ion battery, and the preparation steps of the lithium ion battery include:

[0133] Preparation of positive electrode sheet: positive electrode active material (NCM523), conductive agent (SP), and binder PVDF are mixed and stirred in N-methylpyrrolidone (NMP) at a mass ratio of 98:1:1 to form positive electrode slurry. The prepared slurry is evenly coated on both sides of the aluminum foil and baked to dry. The coated electrode sheet is further cold pressed, stripped, and cut to obtain a positive electrode sheet.

[0134] Preparation of negative electrode sheet: Mix the negative electrode active material graphite, conductive agent (SP), sodium carboxymethyl cellulose (CMC), and binder (SBR) in a ratio of 96:1:1:2 in deionized water to form a uniform slurry. Coat the prepared negative electrode slurry on both sides of the copper foil and bake it dry. Further cold press, strip and cut the coated electrode sheet to obtain the negative electrode sheet of the lithium-ion battery.

[0135] Preparation of electrolyte: Lithium hexafluorophosphate is dissolved in a mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate to prepare an electrolyte, wherein the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1.2:1.9:0.9; the mass percentage of lithium hexafluorophosphate in the electrolyte is 12.8%.

[0136] Preparation of lithium-ion batteries: stack the prepared positive electrode sheet, separator, and negative electrode sheet in order, with the separator placed between the positive and negative electrode sheets, and obtain a bare cell by winding, hot pressing, and ear welding. Place the bare cell in an outer packaging aluminum-plastic film and bake in an oven at 85±10℃ for 24h. Inject the prepared electrolyte into the dried battery, let it stand, form, and divide the capacity to obtain a lithium-ion soft-pack battery.

[0137] Test Case

[0138] (1) Battery safety test

[0139] Test method: Place the battery cell in an oven (hanging test), heat it with convection or circulating hot air at a starting temperature of 25±3℃, and heat the oven temperature at a rate of 5±2℃ / min to 134±1℃, and keep it for 30 minutes before stopping. The battery cell will not catch fire or explode during and after the test.

[0140] The test results are shown in Table 1 below.

[0141] Table 1

[0142]

[0143]

[0144] (2) Battery cycle performance test

[0145] The test steps are as follows:

[0146] 1: Battery storage: time 30min;

[0147] 2: Discharge at 0.5C constant current, cut-off voltage 3.0V;

[0148] 3: Shelf: 5 minutes;

[0149] 4: Charging at 22A constant current, cut-off voltage 4.04V;

[0150] 5: Charge at 15.6A constant current, cut-off voltage 4.12V;

[0151] 6: Charge to 4.35V at 2.3C constant current and constant voltage, cut-off rate 1.8C;

[0152] 7: Charge to 4.48V at 1.8C constant current and constant voltage, cut-off rate 1.5C;

[0153] 8: Charge to 4.56V at 1.5C constant current and constant voltage, cut-off rate 0.74C;

[0154] 9: Shelf: time 5min;

[0155] 10: Charge to 4.51V at 0.8C constant current and constant voltage, cut-off rate 0.05C;

[0156] 11: Shelf: time 5min;

[0157] 12: Discharge at 0.7C constant current, cut-off voltage 3.0V.

[0158] The test results are shown in Table 2 below.

[0159] Table 2

[0160]

[0161] (3) Test of the adhesion between the diaphragm and the electrode

[0162] The test method is as follows:

[0163] (1) Cut the diaphragm into 30*70mm and the electrode into 30*50mm;

[0164] (2) Arrange the silicone pad-white paper-diaphragm (surface to be tested)-electrode-white paper-silicone pad as shown in the figure below and put them into the hot press;

[0165] (3) Set the hot press gauge pressure to 3 MPa, the temperature to 92°C, and the hot press time to 3 min;

[0166] (4) After hot pressing, take out the sample and test the adhesion strength. The peeling width is 30 mm and the peeling speed is 100 mm / min.

[0167] The test results are shown in Table 3.

[0168] Table 3

[0169] Group Diaphragm-cathode (N / m) Diaphragm-anode (N / m) Example 1 11.6 16.0 Example 2 12.9 16.4 Example 3 11.3 12.7 Example 4 11.8 13.1 Example 5 10.1 10.8 Example 6 9.0 9.9 Example 7 9.4 10.3 Example 8 9.5 10.2 Example 9 10.7 11.5 Example 10 10.5 11.2 Embodiment 11 9.1 9.8 Example 12 8.9 9.4 Embodiment 13 8.3 9.0 Embodiment 14 11.2 12.9 Embodiment 15 7.6 8.2 Example 16 7.3 8.0 Embodiment 17 8.0 8.8 Embodiment 18 8.2 8.9 Comparative Example 1 6.7 7.5 Comparative Example 2 4.2 4.9 Comparative Example 3 4.5 4.4 Comparative Example 4 7.4 7.9

[0170] (4) Electrolyte absorption and retention test

[0171] Test method:

[0172] When 10 μL of electrolyte was dripped onto the lithium-ion battery separator, it remained almost unchanged after 1 minute. Therefore, a 1-minute photo was taken to evaluate the electrolyte absorption and retention of the separator and perform quantitative analysis.

[0173] The test results are shown in Table 4 and Figure 1 , 2 .

[0174] Table 4

[0175] Electrolyte Wetting Wetting diameter (mm) Example 1 33.0 Example 2 35.0 Example 3 33.5 Example 4 32.5 Example 5 30.5 Example 6 32.2 Example 7 32.9 Example 8 33.1 Example 9 30.7 Example 10 30.0 Embodiment 11 31.8 Example 12 32.2 Embodiment 13 31.8 Embodiment 14 30.4 Embodiment 15 29.3 Example 16 29.9 Embodiment 17 31.4 Embodiment 18 30.4 Comparative Example 1 19.2 Comparative Example 2 20.2 Comparative Example 3 19.8 Comparative Example 4 22.3

[0176] The above content describes the embodiments of the present invention in detail in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A lithium ion battery separator, characterized in that: The invention comprises a base film and a coating formed on at least one surface of the base film, wherein the coating comprises polymer microspheres and a binder; The particle size D90 of the polymer microspheres is a μm, the particle size D50 of the polymer microspheres is b μm, the particle size D10 of the polymer microspheres is c μm, and the characteristic viscosity of the binder is d dL / g, satisfying: 3.2≤a / d≤175, 1.2≤b / d≤55, and 0.4≤c / d≤10.

2. The lithium-ion battery separator according to claim 1, characterized in that: The particle size D10 of the polymer microspheres is 1 to 2 μm; and / or, The particle size D50 of the polymer microspheres is 3 to 11 μm; and / or, The particle size D90 of the polymer microspheres is 8 to 35 μm.

3. The lithium ion battery separator according to claim 1, characterized in that: The material of the polymer microspheres is selected from at least one of polyethylene, acrylic acid ester copolymer, polystyrene, polyacrylamide, polylactic acid copolymer, polycaprolactone, or modified polymers thereof.

4. The lithium-ion battery separator according to claim 1, characterized in that The intrinsic viscosity of the binder is 0.2 to 2.5 dL / g; and / or, The binder is selected from vinylidene fluoride homopolymer, a copolymer of vinylidene fluoride and at least one selected from hexafluoropropylene, trifluoroethylene, trichloroethylene, chlorotrifluoroethylene, tetrafluoroethylene, vinyl fluoride and monomethyl maleate, and at least one selected from polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane and polyphenylene ether.

5. The lithium ion battery separator according to claim 1, characterized in that: The weight ratio of the polymer microspheres to the binder is 1:3 to 3:

1.

6. The lithium-ion battery separator according to claim 1, characterized in that: The base film has a porous structure; and / or, The base film is selected from at least one of PE, PP, and a composite of PE and PP; and / or, The porosity of the base film is 20% to 50%; and / or, The air permeability of the base film is 30 to 400 sec / 100 cc.

7. The lithium-ion battery separator according to claim 1, characterized in that: The structural morphology of the coating includes one or more of a cellular structure, a granular structure, a bicontinuous structure, a latex structure, and a macroporous structure; and / or, The coating has a thickness of 1 to 10 μm; and / or, The compression rate of the coating is 10% to 70%.

8. A method for preparing a lithium ion battery separator according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polymer microspheres, the binder and the solvent are mixed to obtain a casting solution; the casting solution is coated on a base film, and then immersed in a coagulation bath to solidify to obtain a primary film, and then the solvent in the primary film is removed to obtain the film.

9. The preparation method according to claim 8, characterized in that: The concentration of the casting solution is 2% to 12%; and / or, The coagulation bath comprises water and a non-aqueous solvent in a volume ratio of 2 to 6:1; and / or, The temperature of the coagulation bath is 20-50°C.

10. An electrochemical device, characterized in that The invention comprises a positive electrode, a negative electrode, an electrolyte and a lithium ion battery separator according to any one of claims 1 to 7 or a lithium ion battery separator prepared by the preparation method according to claim 8 or 9.

Citation Information

Cited By

  • Lithium battery positive electrode slurry, positive electrode plate, preparation method and application

    CN120565568A